Theaters and cities. Flânerie between global north-south metropolis on the traces of migrant architectural models (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
Abstract: Theaters around the world are linked by architectural features besides programs and music.The conversation begins by commenting on the concert by Martha Argerich and Daniel Baremboim with the Orchestra Filarmonica della Scala held in Piazza Duomo on May 12, 2016 in Milan. The Concerto in Sol by Ravel is scheduled in the program.The hybrid Neoclassicism of theaters in the modern city between the Eighteenth and Nineteenth centuries: the Teatro alla Scala in Milan - the Teatro Colon in Buenos Aires - the Bolshoi Theater in Moscow - the Sans Souci Theater in Kolkata - the Teatro Massimo in Palermo.Theater in the Palace: The Olympic Theater of Vicenza - The Scientific Theater of Mantua - the San Carlo Theater of Naples - The Metropolitan Opera House Theater of New YorkSouth migration - Global migrationÂ Â